Especiação em Akodon cursor (Winge, 1887): uma abordagem multidisciplinar - Massariol, Cristina Dornelas de Andrade Nogueira (2016)
Akodon cursor (Winge, 1887) is a Sigmodontinae rodent that lives in the Atlantic Forest of Brazil and presents high chromosomal polymorphism (2n=14-16 and NF=18-26), with 31 distinct karyotypes described for this species up to now.Gene sequences of 402 individuals and 63 localities reiterate the geographic structure of A. cursorin North and South clades, with genetic divergence of 4.4% for COI and 2.5% for Cit-b.The phylogeographic break is localized between latitudes 16-18ºS(north Minas Gerais and southern Bahia), coinciding with the Jequitinhonha Valley. The structure of the clades is not related to exclusive karyotypes. However, the form 2n=16 ismore frequent in the North and the form 2n=14 inthe South.Demographic data indicate karyotype contribution on geographic diversification, with populational equilibrium in the North and two distinct and stable populations in the South.Experimental crosses (n=185) involving specimes of A. cursorwith intermediate conditions of geographical distribution (interclades) and karyotype (2n=15),donot indicate reproductive isolation between the Northern clades and Southern clades (reproductive success above 80% ), but show reduced fertility in individuals 2n=15.Combinations (female x male)2n=14x2n=15 and 2n=15x2n=16 show, respectively, higher and lower reproductive success, thusreflecting higher affinity between the forms 2n=15 and 2n=14, and revealing that females 2n=15 presentreproductive disadvantageswhen compared to males in the same heterozygous condition.Moreover, inspecimens with the same diploid number,individuals captured from nature present higher reproductive success than those born in captivity. Aggressive behavior among couples were registered, being more frequent in the Southern clade.There are morphological/anatomical distinctionsbetween individuals of the Northern and Southern clades, in agreementwith the geographical pattern obtained in molecular analysis.Thus, although the use of morphological criteria and reciprocal monophyly points to distinctionsbetweenNorthern and Southern clades showing no signals of reproductive isolation between these populationsis noticeable.The fertility reduction of individuals 2n=15 indicates an incipient process of stasipatric speciation, tending to establish the form 2n=16 in the North andthe form 2n=14 inthe South.Interspecific crosses (n=80) between A. cursorand A. montensis(2n=23-25) Thomas 1913produces sterile hybrids (2n=19-20), unlike observed among supposed A. cursor"hybrid", 2n=15 and interclade.In these cases, the introgression is bidirectional, although ahigher reproductive success (75%) occurred between female of A. montensis2n=24 and male of A. cursor2n=16 (North clade). A. montensiswith 2n=23 14(female), 2n=25 (femaleand male), and A. cursorwith 2n=15 (female) don't generate hybrids.Considering that 2n=14 is aderived condition in A.cursor,and themost frequent in populations of the South clade (which occurs with sympatry with A. montensis), thereexistsa barrier to a more effective gene flow in these areas, with karyotype showing an important role in maintaining the identity of each species